Muscle-splitting mini-incision cholecystectomy under spinal anesthesia: cost-effective equitable minimally invasive surgery in laparoscopy era - Shah, Jay; Mandal, Ram Dayal; Shah, Jenifei; Shah, Jesifei (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Conventional open cholecystectomy has been increasingly replaced by laparoscopy which requires resources for expensive equipment, training, and maintenance. Muscle-splitting mini-incision cholecystectomy under spinal anesthesia has comparable outcomes to laparoscopy and requires fewer resources. This study analyzes the feasibility and outcome of muscle-splitting mini-incision cholecystectomy under spinal anesthesia. Methods: All consecutive cases of muscle-splitting mini-incision cholecystectomy (MC) performed for symptomatic cholelithiasis during three years ending in December 2019, at a periphery hospital in Janakpur, province-2, Nepal, were included. Complicated cholelithiasis (biliary pancreatitis, jaundice, cholangitis, dilated common bile duct) was excluded. Written informed consents were obtained. The need for general anesthesia, complications during and after surgery, and patient satisfaction were analyzed descriptively. Ethical approval was obtained. Results: Out of 148 MC completed under spinal anesthesia, six (4.1%) required fentanyl for shoulder discomfort. Mild post-operative pain was reported by 124 (83.8%) at six hours and 146 (98.6%) at 12 hours. The intravenous drip was stopped after surgery and oral liquid with analgesics started in two hours in 143 patients (96.6%). Post-operative antibiotic was given in nine, for 2(1.4%) cholecysto-duodenal fistulas, 4(2.7%) diabetics, and 3(2%) mucoceles. The mean hospital stay was one night. Wound complications occurred in 6(2.8%). Overall, 144 (97.3%) were satisfied and would recommend the procedure to others. Histopathology revealed adenocarcinoma in one case. There was no bile-duct injury, re-surgery, or mortality. Conclusion: Muscle-splitting mini-incision open cholecystectomy (MC) under spinal anesthesia is safe and effective with early feeding, short hospital stays, less demand for resources, and good patient satisfaction.